Sustainable Business Strategy Through Business Model Canvas to Culinary Business Customer Group at PNM Mekaar Pauh Unit, Padang Regional - Nunung Hidayaty; A. Dewantoro Marsono (International Journal of Scientific Multidisciplinary Research, 2023)
The BMC method can correct errors and provide suggestions for the process of running UMKM in the future. UMKM selling food at Pauh have not shown any improvement, customers who should have naturally gone to the next grade, but the length of time they have been selling is not enough to make them go to the next grade, the object of research is PNM fostered micro-entrepreneurs who sell food at school. The problem to be solved is to look at the BMC. The data collection technique was carried out by distributing questionnaires. While the data analysis technique is descriptive quantitative way. The results of the study show that the value of the channels and cost is quite low